Emerging Natech risk management in Colombia: A survey of governmental organizations. (August 2020) - Suarez-Paba, Maria Camila; Cruz, Ana Maria; Muñoz, Felipe
Highlights: Implications of a regulatory transition into Natech risk management. Identification of gaps and improvement opportunities for Natech risk management. Need and willingness to expand Natech risk knowledge and training. Cooperative efforts required to build on Natech risk management strategies. Technical guidelines for Natech risk management are required. Abstract: There is growing awareness in the international community of the effects of technological accidents triggered by natural hazards, also known as Natechs. Population growth, migration to urban areas, and proximity to industrial developments in hazard-prone areas have aggravated communities' exposure and vulnerability. As a result, governments have started to recognize Natechs as a major risk factor and direct efforts toward the enhancement of Natech risk management strategies. In Colombia, a regulatory transition that incorporates Natech scenarios into the country's disaster risk management strategies has increased stakeholders' risk awareness. Therefore, with the aim of exploring Colombia's current status in Natech risk management and governmental organizations' level of awareness of Natechs, we carried out a questionnaire survey. This paper presents and discusses the notions of Natech risk perception of governmental organizations in Colombia and identifies gaps and improvement opportunities for Natech risk management. The findings highlight the importance of enhancing Natech risk knowledge and training and having cooperative efforts among all stakeholders to build on Natech risk management strategies that promote safer territories. Finally, the results of the survey are compared with the results of an OECD country survey from 2017 in order to analyze Colombia's Natech context in contrast to what other OECD member states have done so far.